Li-Fraumeni syndrome – a case report - Šarac, Sanja; Krsmanović, Željko; Milić, Rade; Radević, Tatjana; Lazović-Popović, Biljana; Vasiljević, Mira; Šarac, Momir (Vojnosanitetski pregled, 2023)
Introduction. Li-Fraumeni syndrome (LFS) is a hereditary familial predisposition to a wide range of certain, often rare malignant diseases. Patients also have an increased risk of developing secondary and even tertiary malignancies throughout their lifetime. The most common malignancies are soft-tissue and bone sarcomas, breast cancer, brain tumors, adrenocortical carcinoma, and acute leukemia. The syndrome is inherited as an autosomal dominant disorder. In most families with LFS, germline mutations of the tumor protein have been identified on the TP53 gene. To our knowledge, this is the second case report of LFS that has been reported in our country so far. Case report. We present five members of the same family with malignant diseases typical for LFS. A woman at the age of 21 had recurrent astrocytoma and mediastinal liposarcoma. Her older sister had rhabdomyosarcoma and liver cancer and died at the age of 18. The mother of their father was diagnosed with breast cancer at the age of 45, and she died at the age of 52. The father’s sister had osteosarcoma and died before the age of 40. The father was diagnosed with lung adenocarcinoma at the age of 49, two years after the death of his second daughter. Genetic analysis identified a pathogenic, heterozygous germline mutation of the TP53 gene. He also has a third, 8-year-old daughter for whom he denied testing for LFS. Conclusion. Genetic analysis for LFS of all family members is required in patients with rare and multiple malignancies but also frequent and early onset malignancies in the family. Screening for the detection of early cancer manifestation is the key to prolonged survival in people with LFS.